PEMBELAJARAN KOSAKATA (MUFRADÄ€T) BAHASA ARAB MELALUI MEDIA GAMBAR UNTUK MENINGKATKAN MINAT BELAJAR MAHASISWA PADA JURUSAN PAI FAKULTAS TARBIYAH IAIN PALU - Sitti Hasnah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2015)
This study aims to determine the role of pictures media used in learning vocabulary (mufradÄt), to determine the interest of students towards Arabic vocabulary learning (mufradÄt), and to determine the use of pictures media to increase the interest of Arabic vocabulary learning (mufradÄt). This study used quantitative descriptive approach. The data were collected using a test instrument, documentation, and a questionnaire for Arabic vocabulary learning data (mufradÄt) and data regarding student interest in learning. The data obtained through such tests were analyzed by using tests and the data were analyzed using student interest descriptive statistics. The results showed that the average value of the test before using the pictures media is low with a score of 5.25 and a standard deviation of 1.5. While the results of the test after using pictures media is high with an average of 7 and a standard deviation of 1.3. From the results obtained by the researcher suggests the teacher should use the pictures media in presenting the material in Arabic as one of the strategies in Arabic vocabulary learning (mufradÄt). Besides teachers to be more creative and innovative in presenting Arabic learning in order to improve spirit and learning achievement